Comparison of Osteogenic Differentiation in Mouse Calvarial Pre-Osteoblasts Treated with Conditioned Media from 2D- and 3D-Cultured Human UC-MSCs - Won-Jung Bae; Sang-Im Lee (치위생과학회지)
Background: Umbilical cord-derived mesenchymal stem cells (UC-MSCs) have emerged as a promising cell source for regenerative medicine owing to their high proliferation rate, low immunogenicity, and strong paracrine effects. However, the majority of transplanted stem cells undergo rapid clearance in vivo, limiting their direct regenerative effects. To overcome this, cell-free approaches using the secretomes of UC-MSCs—especially those from three-dimensional (3D) spheroid cultures—have gained attention for their enhanced therapeutic potential. Methods: UC-MSCs were cultured under two-dimensional (2D) or 3D spheroid conditions. The conditioned media (CM) were collected from each group and applied to mouse calvarial pre-osteoblasts. The osteogenic differentiation potential was evaluated by analyzing the expression of key osteogenic markers (Dlx5, Osx, ALP, BSP, OPN, Sost, DMP1, and Phex) at days 1 and 3, using qRT-PCR. Results: CM from the 3D-cultured UC-MSCs did not enhance the expression of any of the osteogenic transcription factors relative to that achieved using osteogenic induction medium (OS, positive control) on days 1 or 3. Osx expression was consistently higher in the 3D CM group than in the 2D CM group, although it did not vary significantly between the 3M and OS groups. Early- to mid-stage osteogenic markers (BSP, ALP, and OPN) were significantly upregulated in the 3D CM group on day 1, with BSP and OPN remaining elevated on day 3. The expression of Sost—a marker of mineralization and osteocyte maturation— on day 3 was highest 3D CM treatment. Conclusion: CM from 3D-cultured UC-MSC spheroids promoted osteogenic differentiation of pre-osteoblasts more effectively than that derived from 2D cultures. This suggests the 3D-cultured UC-MSC secretome may serve as a promising cell-free therapeutic strategy for bone tissue regeneration. Further in vivo studies and mechanistic investigations are required to validate its clinical potential.